(untitled) (Journal of the College of Basic Education, 2026)
The relationship between the Ottoman Sultan Abdul Hamid II and the Armenian issue of the Ottoman state was described as one of the most tense and complex issues in the history of the Ottoman state, especially during the reign of this Sultan. During this period, pressures began from the Armenians and European countries to force the Sultan to carry out a set of reforms in the areas inhabited by the Armenians. Sultan Abdul Hamid considered these demands to be nothing but the beginning of the division of the Anatolian regions and a pretext used by European countries to interfere in the affairs of the Ottoman state and then the independence of the Armenians. As a result of the Sultan’s rejection of any attempts to reform their conditions, violent confrontations and the extermination of many Armenians occurred as a result of the clashes that took place between the Armenians and the Ottoman government. This reached the point of an assassination attempt against Sultan Abdul Hamid II in 1905, and even reached the point of the Armenians joining and supporting the Committee of Union and Progress, which contributed to the overthrow of the government of Sultan Abdul Hamid II in 1908.